Loosened hip joint prosthesis-decision options - Byser Bonchev; Tsvetoslav Yordanov; Luben Stokov; Teodor Ivanov; Georgi Georgiev; Luben Lubenov Stokov; Kristian Nastev (Journal of the Bulgarian Orthopaedics and Trauma Association)
For the period 2013-2015, 36 patients underwent revision surgery because of secondary developed complications after primary hip joint replacement surgery. 14 of them were male and 23 – female, with average age 73 years.